Semi-open Mandapa of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The Neelkanth Mahadev Temple has a semi-open mandapa (pillared hall). It has four pillars at its centre and dwarf walls all along its sides. Facing the garbhagriha (sanctum sanctorum), there is a Nandi sculpture on a pedestal at the centre of the mandapa. The pillars and the interior walls of the mandapa are plain.